Women's rights and development policies in India - Sujaya, C.P. (1995)
"This paper traces the shifts in policy approaches that have taken place in India towards issues regarding women and their development from the post independence period till the present. It critically reviews the achievements and nature of shortcomings and identifies certain measures that need to be taken to ensure that `a paradigm shift' takes place from what constitutes `a positive agenda for action' to `a charter of rights'"
Keywords: Women's rights - India; Women - India